RNAi-mediated pathways in the nucleus. - Matzke, M.A.; Birchler, J.A. (Nature Reviews. Genetics, 2005)
RNA interference (RNAi) is an evolutionarily conserved mechanism that uses short antisense RNAs that are generated by 'dicing' dsRNA precursors to target corresponding mRNAs for cleavage. However, recent developments have revealed that there is also extensive involvement of RNAi-related processes in regulation at the genome level. dsRNA and proteins of the RNAi machinery can direct epigenetic alterations to homologous DNA sequences to induce transcriptional gene silencing or, in extreme cases, DNA elimination. Furthermore, in some organisms RNAi silences unpaired DNA regions during meiosis. These mechanisms facilitate the directed silencing of specific genomic regions.